MG-103 Determining genetics referral eligibility for hereditary breast/ovarian cancer risk assessment: An electronic solution. (4th December 2015) - Meschino, Wendy; Honeyford, Joanne; Huang, Tianhua; Ambus, Ingrid; Misinai, Michael; Robinson, Stephanie; Muraca, Maria; Doreen, Saint
Abstract : Objectives: To develop and validate an electronic tool to enhance referrals to the Familial Breast/Ovarian Cancer Clinic. Design/methods: Patients attending the Breast Diagnostic Clinic were recruited for this non-randomised 3-phase study, where paper questionnaires (PQ) and surgeon assessments were traditionally used to determine Genetics referral eligibility. Phase 1 : Patients completed PQ (N = 201). Phase 2 : Electronic tool (ET) developed; tested for usability, readability, design, interface. Tool accuracy assessed by comparing results for patients completing both PQ and ET (N = 100). Phase 3 : Patients completed ET only (N = 200). Health records reviewed to determine data accuracy. Number of study patients eligible for referral compared with referrals received across all 3 phases. Patient/provider satisfaction assessed. Results: Gender, education, number of patients with breast/ovarian cancer, age at diagnosis, family history, proportion of patients meeting referral criteria were similar across all study phases. No statistically significant difference in either number of patients eligible for referral or overall referral rates (Phase 1: 16.9%; Phase 3: 18.0%) was found. 67% of patients preferred ET over PQ. Patients found ET questions easier to complete and understand. Physician satisfaction was higher with ET in reviewing family history, identifying eligible patients, making timely referrals. Conclusions: The electronic tool was accurate and useful in determining referral eligibility. Similar referral rates were seen across study phases. Patients and physicians had positive experiences with the ET. It is feasible to use this tool to identify patients eligible for Genetics referral. Further studies are in progress to investigate why some eligible patients were not referred.